1927 Haw. Sess. Laws 209-217, AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), § 20 - (:unkn) unknown (General Publisher, 1927)
Required the sheriff to keep books containing all information furnished to him relative to ownership, acquisition, importation, delivery, and possession of firearms and ammunition. Copies of the book will be made for the Governor twice per year.
--
Keywords: REGISTRATION